Full spectrum cannabidiol-rich extract reduced propofol dosage required for anesthetic induction in dogs—a pilot study - Hasckel Gewehr, João Lourenço; Enzele, Maria Laura; Freiria, Lucas Marlon; Nunes, Morgana Martins; Spengler, Júlia; Dondoerfer Teixeira, Ana Paula; Amazonas, Erik; Sasso Padilha, Vanessa (Frontiers in Veterinary Science, 2024)
Cannabinoids show great therapeutic potential, but their effect on anesthesia still remains unclear. Use of chronic recreational Cannabis in humans undergoing anesthetic procedures tends to require a higher dose when compared to non-users. On the other hand, studies on rodents and dogs have shown that cannabinoid agonists may potentiate certain anesthetics. This contrast of effects possibly occurs due to different time lengths of administration of different phytocannabinoids at different doses, and their distinct effects on the Endocannabinoid System, which is also affected by anesthetics such as propofol and isoflurane. This randomized, double blind, placebo controlled study evaluated the effects of 2 and 6 mg/kg of phytocannabinoids in a full spectrum Cannabidiol-rich extract (fsCBD-rich extract) administered transmucosally as a single-dose at 75 minutes before induction with propofol in healthy male dogs undergoing neutering. Preanesthetic medication protocol was also included across all treatment groups, 15 minutes before induction. In our study, 6 mg/kg of total phytocannabinoids were able to reduce the dose of propofol necessary for induction by 23% when compared to the control group. Heart and respiratory rate, blood pressure, temperature and sedation were evaluated prior to, and at 30, 60 and 75 min after administration of the fsCBD-rich extract or Placebo extract. The fsCBD-rich extract did not produce significant sedation within or between groups, although statistically significant differences in heart rate and systolic blood pressure were found. Our findings indicate that phytocannabinoids could be an adjunct option in anesthesia, although further research is necessary to better confirm this data. Additionally, further research is needed to determine the best dosage, delivery method, time for administration, ideal molecular profile for desired effects, safety, drug-drug interactions,and transurgical effects.Objective: Evaluate the impact of a single-dose of 2 mg/kg or 6 mg/kg of total phytocannabinoids administered transmucosally 75 minutes before anesthetic induction, on the anesthetic effects of propofol induction in healthy male dogs undergoing elective orchiectomy.